The development of border states during the Algerian revolution 1959/1962 - sid ali, ahmed mesoud (Journal of Social Sciences and Humanities, 2019)
This study is an attempt to monitor the positions of the various field leaders of the Border States during the Algerian revolution between the years 1959/1962. We refer to the frontier states, the fifth, and the sixth in view of the main role played in the field of supply of arms and gear and face the line of "Morris" and "shawl" The intensity of the pressure imposed by the French military occupation administration during the same period, when it detected its military and political potential to eliminate the Algerian revolution, whether through the program of the Hellenic War which began in February 1959, or through General Program, From the "Peace of the Brave" program to the attempts to separate the Sahara and drag the National Liberation Front towards negotiations ending with the independence of the missing, and therefore the position of the leaders of the interior was betting on him by the interim government starting from the border states that had to face the electrified lines and intensify military operations and coordinate their efforts with the Staff The instructions passed by the interim government towards the rest of the internal states were passed to impose new balance of power that would give the armed struggle of the Algerian revolution dynamic and effective, which would then accelerate the issue of negotiations, The sole legitimate and representative of the Algerian people, represented in the interim government of the Algerian revolution. This study, which includes an equal survey of the most prominent border states during the Algerian revolution, will bring us closer to defining the implications of the revolutionary act practiced by leaders and representatives, indicating the developments and interactions of each period and the extent of the military dimension, And the tactics of the French generals. Our research experience in this article will also monitor the difficult birth consequences of the sixth state between 1954 and 1956, by standing at the first stage of the installation of Maj. Ali Mallah on her pyramid, through some harsh backgrounds that led to the settling of accounts with some leaders, And the fifth as a result of circumstances that resulted from the developments of the armed struggle movement, not to mention the entry of this state another phase of its experience, is to consecrate its legitimacy in alliance with the General Staff. The Algerian revolution will thus not disappear its achievements behind the misjudgments and understanding of the status quo, but by going through all stages, including maneuvers of the occupation, has entered the turning point of the crucial negotiations, to resolve the stage of a minuscule history of struggle, and enter later period will emerge Where it was not padded, and disappears what was prominent and advertised. Therefore, our study presented a series of results. The talk about the role of the historic border states during the liberation revolution is mainly talk about their field effectiveness in providing weapons and generalizing them to the regions as a whole. The Border States really have been assembled by the problem of weapons, and their division of leadership. The state of these states was almost the same, all of them tainted by the horrors of colonial schemes, but it was a kind of rigidity and tactics, as in the early days of the Algerian liberation revolution. The gradual development witnessed by the liberation revolution at the level and the emergence of personalities and leaders in the most difficult circumstances placed them on a hot plate. This necessitated the adoption of the logic of wisdom in completing the path towards negotiations and making the project of national independence the desired Means and methods